2015
DOI: 10.2527/jas.2015-9019
|View full text |Cite
|
Sign up to set email alerts
|

Altering ewe nutrition in late gestation: I. The impact on pre- and postpartum ewe performance1

Abstract: The present study was conducted to examine the effects of offering a single diet rationed to 80% (80% ME), 100% (100% ME), or 120% (120% ME) of recommended ME requirements from d 119 of gestation to lambing, with concurrent changes in other dietary nutrients. The effects on pre- and postpartum ewe performance, including estimated milk yield and milk fatty acid concentrations, were monitored. Sixty twin-bearing ewes were allocated to 1 of 3 dietary treatments ( = 20 per treatment) and individually fed for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 59 publications
4
31
2
Order By: Relevance
“…Previous studies have demonstrated the utilization of body fat reserves by the ewe to preserve circulating concentrations of glucose during periods of nutrient restriction, thus maintaining fetal growth (Tygesen et al, 2008). This is supported, in the present study, by a marked reduction in BCS between ewes allocated to the restricted and excessive energy treatments (McGovern et al, 2015) coupled with the lack of difference seen in blood glucose concentration, organ size and, ultimately, birth weight of the offspring. It may be that the ewe yielded her own body reserves to ensure optimal fetal growth during the final stage of gestation.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Previous studies have demonstrated the utilization of body fat reserves by the ewe to preserve circulating concentrations of glucose during periods of nutrient restriction, thus maintaining fetal growth (Tygesen et al, 2008). This is supported, in the present study, by a marked reduction in BCS between ewes allocated to the restricted and excessive energy treatments (McGovern et al, 2015) coupled with the lack of difference seen in blood glucose concentration, organ size and, ultimately, birth weight of the offspring. It may be that the ewe yielded her own body reserves to ensure optimal fetal growth during the final stage of gestation.…”
Section: Discussionsupporting
confidence: 76%
“…Studies have outlined the influence of both maternal BCS and gestational nutrition on lamb birth weight (Gardener et al, 2005;Kenyon et al, 2009;Caton and Hess, 2010;Meyer et al, 2010), highlighting its importance in the detection of fetal growth restriction and/or adequate maternal nutrition. In the present study, despite the difference in ewe DMI and BCS (McGovern et al, 2015), there was a lack of difference observed in lamb birth weight. Initially, this highlighted the apparent adequacy of nutrition received by the ewes on each of the 3 dietary treatments and contradicted the earlier findings of Russel et al (1977), who reported that a moderate degree of undernourishment in late gestation resulted in the reduced weight of twin lambs at birth.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations